Validation of Two Nonlinear System Identification Techniques Using an Experimental Testbed - V. Lenaerts; G. Kerschen; J.-C. Golinval; M. Ruzzene; E. Giorcelli (Shock and Vibration)
The identification of a nonlinear system is performed using experimental data and two different techniques, i.e. a method based on the Wavelet transform and the Restoring Force Surface method. Both techniques exploit the system free response and result in the estimation of linear and nonlinear physical parameters.